Curcumin‐loaded PHB/PLLA nanofibrous scaffold supports osteogenesis in adipose‐derived stem cells in vitro. (6th May 2021) - Abazari, Mohammad Foad; Zare Karizi, Shohreh; Hajati‐Birgani, Nazanin; Kohandani, Mina; Torabinejad, Sepehr; Nejati, Fatemeh; Nasiri, Navid; Maleki, Mohammad Hossein; Mohajerani, Hassan; Mansouri, Vahid
Abstract: One of the most important goals of bone tissue engineering is to regenerate damaged tissue and improve its function by making three‐dimensional scaffolds. This role becomes more important and efficient when it can release a biologically active factor at the site of the lesion. In the present study, poly(3‐hydroxybutyrate)/poly(l ‐lactic acid) nanofibers (PHB/PLLA) and curcumin‐incorporated PHB/PLLA nanofibers (cur‐PHB/PLLA) were fabricated using electrospinning. After morphological and biological characterization, and Curcumin release assessment, the osteogenic differentiation potential of the human adipose–derived stem cells (ADSCs) was investigated with the evaluation of the common osteogenic markers. Fabricated nanofibers were smooth, bead free, and with continuous release of curcumin. The biocompatibility of the fabricated nanofibers was improved while incorporated with curcumin compared to the empty nanofibers. Besides, evaluation of the alkaline phosphatase (ALP) activity, calcium content, and osteogenic‐related gene expression revealed that the PHB/PLLA mat can support osteogenic differentiation of the ADSCs more efficiently while incorporated with curcumin. Based on the results, it can be concluded that cur‐PHB/PLLA has promising potential for use in the treatment of the bone lesions and/or bone tissue engineering.